Menstrual cycle and the temporal discrimination threshold. (18th January 2017) - Mc Govern, Eavan M; O'Connor, Emer; Beiser, Ines; Williams, Laura; Butler, John S; Quinlivan, Brendan; Narasimham, Shruti; Beck, Rebecca; Reilly, Richard B; O'Riordan, Sean; Hutchinson, Michael
Abstract: The temporal discrimination threshold (TDT) is a proposed pre-clinical biomarker (endophenotype) for adult onset isolated focal dystonia (AOIFD). Age- and sex-related effects on temporal discrimination demonstrate that women, before the age of 40 years, have faster temporal discrimination than men but their TDTs worsen with age at almost three times the rate of men. Thus after 40 years the TDT in women is progressively worse than in men. AOIFD is an increasingly female-predominant disorder after the age of 40; it is not clear whether this age-related sexually-dimorphic difference observed for both the TDT and sex ratio at disease onset in AOIFD is a hormonal or chromosomal effect. The aim of this study was to examine temporal discrimination at weekly intervals during two consecutive menstrual cycles in 14 healthy female volunteers to determine whether physiological hormonal changes affected temporal discrimination. We observed no significant differences in weekly temporal discrimination threshold values during the menstrual cycles and no significant correlation with the menstrual cycle stage. This observed stability of temporal discrimination during cyclical hormonal change raises interesting questions concerning the age-related sexually-dimorphic decline observed in temporal discrimination. Our findings pave the way for future studies exploring potential pathomechanisms for this age-related deterioration.